Long-term follow-up of a randomized study of combination interferon and glatiramer acetate in multiple sclerosis: Efficacy and safety results up to 7 years - Lublin, Fred D.; Cofield, Stacey S.; Cutter, Gary R.; Gustafson, Tarah; Krieger, Stephen; Narayana, Ponnada A.; Nelson, Flavia; Salter, Amber R.; Wolinsky, Jerry S. (Multiple sclerosis and related disorders, 2017)
To report the long-term results of the blinded extension phase of the randomized, controlled study of the combined use of interferon beta-1a (IFN) 30μg IM weekly and glatiramer acetate (GA) 20mg daily compared to each agent alone in relapsing-remitting multiple sclerosis (RRMS). 1008 RRMS patients were followed on protocol until the last participant enrolled completed 3 years, allowing some subjects to be followed for up to 7 years. The primary endpoint was reduction in annualized relapse rate. Secondary outcomes included time to confirmed disability, Multiple Sclerosis Functional Composite (MSFC) score and MRI metrics. Similar to the core study, combination IFN + GA was not superior to the better of the single agents (GA) in risk of relapse. Both the combination therapy and GA were significantly better than IFN in reducing the risk of relapse. The combination was not better than either agent alone in lessening confirmed EDSS worsening or change in MSFC. Also similar to the core result, the combination was superior to either agent alone in reducing new lesion activity, but the 3 year MRI result did not presage a clinical benefit over the extended observation interval. Combining GA & IFN did not produce a significant clinical benefit over the entire study duration. The earlier effect on reducing MRI activity did not result in a later clinical advantage. The combination showed a sustained advantage in reducing disease activity free status. •The CombiRx trial has been the longest per protocol MS clinical trial to date.•No unique combination side effects or safety issues.•GA was superior to IFN in reducing the risk of exacerbation, but not in any of the other clinical measures.•The combination was not better than single agents clinically but was superior in reducing MRI activity.•The combination was superior to either agent in the percentage achieving DAFS, driven by the MRI effects.